PENGARUH REWARD TERHADAP MOTIVASI BELAJAR AKIDAH AKHLAK SISWA DI MIN SIHADABUAN PADANGSIDIMPUAN - Rini Rini Agustini (Universitas Muhammadiyah Tapanuli Selatan, 2018)
Reward is an Islamic educational tool that can motivate students to learn. However, the motivation of students to learn Aqidah Morals in MIN Sihadabuan looks declining. This can be seen from students who are less excited when following the learning process so that the value of repetition obtained by learners is under the KKM. Therefore, giving rewards is one that can be done by a teacher to encourage students to get a good achievement. Reward is an effective and strategic way when used in accordance with the principles of learning to stimulate learners to be more active in learning and to develop the potential of learners. Thus it is expected that the motivation of learners in the learning process will increase and increase.The problem is whether there is a significant influence on the motivation to motivate learning Aqidah Akhlak students simultaneously in MIN Sihadabuan Padangsidimpuan? The purpose of this study is to determine whether there is a significant influence on the motivation of motivation to learn Aqidah Akhlak students simultaneously in MIN Sihadabuan Padangsidimpuan.The results of this study there is a significant effect of reward on student learning motivation of 0.715, the contribution of 51.1225% the remaining 48.8775% is determined by other variables. This provides information that rewards have a strong effect on student learning motivation. This provides information that rewards simultaneously have a strong influence on student learning motivation. Keywords: Reward and motivation to learn.